Malaysian general music teachers’ attitudes and practices in multicultural music education - Wong, K.Y. (2015)
The awareness of the importance of multicultural music in the Malaysian primary music education has increased due to the requirements set by the National Curriculum Standards for Primary School in music education in Malaysia. Therefore, it can be said that multicultural music is not an optional component to be included or disregarded at the discretion of the teacher in the music classroom. Music teachers are expected to foster multicultural music educational programs that address the diverse needs of students. in the context of sustainability of multicultural music education, it is important to know that the current status of music teachers’ attitudes and practices with regard to multicultural music education such as what and how effective are the practices and their perceptions as far as the multicultural music is concerned. Therefore, this study examined Malaysian general music teachers’ utilization of multicultural music education in the music curriculum, specifically exploring the relationship between the general music teachers’ attitudes and their efforts in developing and implementing multicultural music education in music classes. This study utilized an adaptation of the original Music Specialist’s Multicultural Music Education Survey instrument which was administered to 456 of primary schools’ general music teachers in Malaysia. This instrument was used to measure teachers’ attitudes and practices regarding multicultural music education. Data analysis included descriptive statistics, analysis of variance (ANOVA) and correlational analysis (pearson product-moment correlation). Results indicate that there is limited implementation of multicultural music education in the music classrooms due to inadequate preparation and limited resources, and insufficient knowledge in multicultural music. As such, it is important to ensure music teachers develop a more critical understanding of multicultural music education include producing and developing more instructional materials and learning aids, which are suitable for primary students and appropriate for the Malaysian context. Hence, music teacher training programs are needed in order to address both theoretical and practical aspects of multicultural music education throughout the curriculum in a comprehensive and long-term manner.